Flexible Work Supervision and Harmonious Relationships: A Qualitative Study of Non-Physical Work Environment in Rural Indonesia - Diana Novita; Rita Murtiarni (Indonesian Journal of Cultural and Community Development, 2023)
This qualitative study aims to provide a descriptive overview of the non-physical work environment at a Village-Owned Enterprise (BUMDes) in a rural area of Indonesia. Using in-depth interviews with three informants, the research examines the flexible job supervision system, responsibility prioritization, periodic monitoring, and comfortable working atmosphere at BUMDes Tanjung Lestari. The findings reveal harmonious relationships among BUMDes management, village officials, and members, contributing to a conducive work environment. This study sheds light on effective work supervision approaches and interrelated dynamics within rural community enterprises, suggesting potential implications for sustainable and cooperative work environments. Highlight: Descriptive Overview: The study provides a comprehensive understanding of the non-physical work environment at a rural Village-Owned Enterprise (BUMDes) in Indonesia. Flexible Supervision: The research explores a flexible job supervision system, highlighting its impact on work processes and outcomes. Harmonious Relationships: The study uncovers the harmonious relationships between BUMDes management, village officials, and members, contributing to a conducive work environment. Keyword: Non-Physical Work Environment, Village-Owned Enterprise (BUMDes), Flexible Supervision, Harmonious Relationships, Sustainable Work Environment